Students’ Competence Needs Analysis in Curriculum for Facing 21st Century Education - Sudung Nainggolan (STAI Hubbulwathan Duri, 2022)
This study aims to determine the competency needs of students in curriculum design to face the challenges of 21st-century education. This study uses a qualitative approach. The subjects of this research are postgraduate students at one of the private universities in Batu City who are currently pursuing masters and doctoral education. Data was collected through interviews and questionnaires. Data analysis in this study consisted of several flow activities carried out together, namely data reduction, data presentation, and conclusion drawing/verification. The results of the study conclude that student competencies that must be designed in the higher education curriculum to face the challenges of 21st-century education must pay attention to three aspects, including; creating new value, reconciling tensions and dilemmas, and responsibilities. So, the curriculum framework that must be made includes cognitive skills, social and emotional skills, and practical skills. The results of this study also have implications for the understanding of higher education related to the development of human life and science, because the curriculum created can meet student competencies in the future